Sistem Pendukung Keputusan Latihan Memanah Menggunakan Algoritma Decision Tree - Muhammad Fikri Hidayattullah; Taufik Abidin; Ismi Nururrizqi Nururrizqi; Ianatul Khoeriyah (Komputika : Jurnal Sistem Komputer, 2021)
Archery sports become one of the favorite sports of the people of Indonesia. From here then emerged various places to practice archery. Only complete activities carried out that activate the weather, temperature and temperature factors at the training ground. While students who will practice archery have brought quite a lot of homes and sometimes the distance of the house to the practice site is relatively far. Based on these conditions, this research will develop a decision support system that can predict the implementation of training in accordance with weather criteria, wind conditions and temperature. This Decision Support System applies a tree decision algorithm and is implemented into the website.